Mitochondrial DNA corroborates the species distinctiveness of the Planalto (Thamnophilus pelzelni Hellmayr, 1924) and the Sooretama (T. ambiguus Swainson, 1825) Slaty-antshrikes (Passeriformes: Thamnophilidae) - Lacerda, Daniela Rodrigues (2007)
ABSTRACT: The Thamnophilus punctatus complex has been recently reviewed on the basis of morphological and vocal characters, and is divided in six different species. Two of the new species, although well defined on the basis of morphological differences, could not be unambiguously distinguished through their loudsongs. The Planalto Slaty-antshrike (Thamnophilus pelzelni) and the Sooretama Slaty-antshrike (T. ambiguus) are most easily distinguished by subtle and localized changes in plumage colors of males and females. In the present study we used sequences of the control region, Cytochrome b, and ND2 genes, of the mitochondrial DNA (mtDNA) to evaluate the levels of molecular differentiation between these two species. The mean pairwise distance between the two species was 3.8%, while it varied from 2.7% to 4.9% for each mtDNA region. Although extensive variation was also detected among haplotypes within species, especially for T. ambiguus, we suggest that the genetic divergence found between T. ambiguus and T. pelzelni is high enough to corroborate the separate species status of these two antbird taxa. _______________________________________________________________________________ RESUMO